Structural equations the effect of logical-critical thinking style with academic achievement with the mediating role of action control in high school students - Abdollahi , Masoome; Darbani, Seyed Ali; Parsakia , Kamdin (Journal of Assessment and Research in Applied Counseling (JARAC), 2022)
Background and Aim: So far, several psychological and social multivariate models have been investigated to predict students’ academic progress on the eve of the entrance exam. This research was conducted to investigate the effect of logical-critical thinking style on academic achievement with the mediating role of action control in entrance exam students. Methods: This was descriptive correlational research. The statistical population included all entrance exam students in East Tehran in 2019. At first, a sample of 400 people was selected by the multi-stage cluster sampling method. However, the final analysis was done on 356 entrance exam students. The research tools included Ricketts’ Critical Thinking Disposition Scale (2003), Epstein and Pasini’s (1999) rational-scale, Pham and Taylor’s (1994) academic performance questionnaire, and Diefendorf et al.’s (2000) action control scale. The data were analyzed with the help of SPSS and LISREL software and using the structural equation modeling method. Results: The research findings showed that the model related to the relationship between logical-critical thinking style and academic achievement is a good fit considering the mediating role of action control. Also, the research findings showed that 23% of the observed variance in academic progress could be explained through logical thinking, and 26% could be explained through critical thinking. Conclusion: The findings show the mediating role of action control in the relationship between logical-critical thinking style and academic achievement. Therefore, it seems necessary to consider the role of these variables by experts, academic advisors, and planners when working with entrance examination students, specifically in educational and entrance examination centers and institutions.